Analysis of the Energy and Mineral Source Regulation in the Formulation of Job Creation Law (Omnibus Law) - Indah Dwi Qurbani; Muhammad Rafid Zuhdi (Fakultas Hukum Universitas Lampung, 2020)
This research is an analysis and evaluation of the Work Creation Omnibus Law. The intended Work Creation Act regulates many sectors, in this study an evaluation and analysis of the omnibus law in the energy and mineral resources sector is carried out as regulated and contained in paragraph five of the Work Creation Act. This has resulted in pros and cons and has become an issue of national law. The omnibus law method is not completely new to Indonesia. The substance of the omnibus law has been used in the legislative process in Indonesia. In terms of the formation Law Number 23 of 2014 concerning Regional Government, it is a form of omnibus law. The type of research in this research is normative legal research, with the nature of prescriptive and applied research with the aim of evaluating and analyzing the energy and mineral resources sector regulations on the formation of the Work Creation Act.